2013
DOI: 10.1002/hep.26328
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib perpetuates cellular anticancer effector functions by modulating the crosstalk between macrophages and natural killer cells

Abstract: Alternatively polarized macrophages (MU) shape the microenvironment of hepatocellular carcinoma (HCC) and temper anticancer immune responses. We investigated if sorafenib alters the HCC microenvironment by restoring classical macrophage polarization and triggering tumor-directed natural killer (NK) cell responses. In vivo experiments were conducted with sorafenib (25 mg/kg)-treated C57BL/6 wildtype as well as hepatitis B virus (HBV) and lymphotoxin transgenic mice with and without HCC. Monocyte-derived MU or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 42 publications
4
123
0
Order By: Relevance
“…In mice, sorafenib reduced the number of NK cells and their activity against tumor cells (40). However, others have noted that short-term administration of sorafenib activates hepatic NK cells through activation of tumor-associated macrophages (41) and that sorafenib inhibits the shedding of major histocompatibility complex class I-related chain A (MICA), an NKG2D ligand (42). We found that expanded NK cells considerably enhanced the antitumor cytotoxicity of sorafenib and that NK-cell cytotoxicity appeared to be unaffected regardless of whether sorafenib was added to the cultures, suggesting that a combination of sorafenib plus expanded NK cells could have additive antitumor effects in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, sorafenib reduced the number of NK cells and their activity against tumor cells (40). However, others have noted that short-term administration of sorafenib activates hepatic NK cells through activation of tumor-associated macrophages (41) and that sorafenib inhibits the shedding of major histocompatibility complex class I-related chain A (MICA), an NKG2D ligand (42). We found that expanded NK cells considerably enhanced the antitumor cytotoxicity of sorafenib and that NK-cell cytotoxicity appeared to be unaffected regardless of whether sorafenib was added to the cultures, suggesting that a combination of sorafenib plus expanded NK cells could have additive antitumor effects in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…59,113,114 Other suppressive cells that are abundant in tumors including HCC, such as myeloid-derived suppressor cells and M2-polarized tumor-associated macrophages, also suppress the expression of NK cell-activating receptors and impair NK cell function by secreting TGF-b and IL-10 or IDO. 17,48,115 In addition, tumor-associated fibroblasts prevent IL-2-induced upregulation of the activating receptors NKp44, DNAM-1 and NKp30, which depend on cell-to-cell contact and PGE2 release; thus, tumor-associated fibroblasts strongly inhibit NK-cell function. 116 Similar studies have also reported that HCCassociated fibroblasts trigger NK cell dysfunction via PGE2 and IDO.…”
Section: Nkr Expression By Inhibitory Cytokinesmentioning
confidence: 99%
“…We read with great interest the article of Sprinzl et al 1 in HEPATOLOGY. The group highlighted the antitumoral effects of sorafenib in hepatocellular carcinoma (HCC) from an immunological point of view.…”
Section: Interplay Between Cancer Cells Macrophages and Natural Killmentioning
confidence: 99%